Enhanced capture and release of circulating tumor cells using hollow glass microspheres with a nanostructured surface. Issue 35 (30th August 2018) - Dong, Ziye; Yu, Dan; Liu, Qingye; Ding, Zhenya; Lyons, Veronica J.; Bright, Robert K.; Pappas, Dimitri; Liu, Xinli; Li, Wei
Abstract : NS HGMS can isolate and recover circulating tumor cells in blood with shorter processing time, enhanced capture efficiency and lower detection limit. Abstract : Self-floating hollow glass microspheres (HGMS) modified with tumor-specific antibodies have been developed for the capture of circulating tumor cells (CTCs), and have demonstrated effective cell isolation and good viability of isolated cancer cells. However, the capture efficiency decreases dramatically if the spiked cell concentration is low, possibly due to insufficient interactions between cancer cells and the HGMS surface. In order to apply HGMS-based CTC isolation to clinically relevant samples, it is desirable to create nanostructures on the surface of HGMS to enhance cell-surface interactions. Nevertheless, current microfabrication methods cannot generate nanostructured-surfaces on microspheres. The authors have developed a new HGMS with a controlled nanotopographical surface structure ( NS HGMS), and demonstrated isolation and recovery of rare cancer cells. NS HGMS are achieved by applying layer-by-layer (LbL) assembly of negatively charged SiO2 nanoparticles and positively charged poly-l -arginine molecules, then sheathing the surface with an enzymatically degradable LbL film made from biotinylated alginate and poly-l -arginine, and capping with anti-EpCAM antibodies and anti-fouling PEG molecules. Compared to smooth-surfaced HGMS, NS HGMS showed shorter isolation time (20 min), enhanced capture efficiency (93.6 ± 4.9%) and lower detection limit (30 cells per mL) for commonly used cancer cell lines (MCF7, SK-BR-3, PC-3, A549 and CCRF-CEM). This NS HGMS-based CTC isolation method does not require specialized lab equipment or an external power source, and thus, can be used for the separation of targeted cells from blood or other body fluids in a resource-limited environment.